COVID-19 vaccination and Guillain-Barré syndrome: analyses using the National Immunoglobulin Database. Issue 9 (12th August 2022) - Keh, Ryan YS; Scanlon, Sophie; Donegan, Katherine; Cavanagh, Sally; Foster, Mark; Skelland, David; Palmer, James; Machado, Pedro M; Carr, Aisling S; Lunn, Michael P
Abstract : Anti-viral vaccination has rarely been associated with Guillain-Barré syndrome(GBS). We performed a population-based study of NHS England data and a UK multicentre surveillance study to investigate the relationship between COVID-19 vaccination and GBS. We linked GBS cases from England's National Immunoglobulin Database(NID) with COVID-19 vaccina- tion data from December 2020–July 2021. GBS temporally associated within a 6-week risk window of any COVID-19 vaccine was identified. We prospectively collected incident UK GBS cases January–November 2021 regardless of vaccine exposure. The NID recorded 996 English GBS cases January–October 2021. A spike of cases above the 2016-2020 average occurred March–April 2021. 198 cases occurred within 6 weeks of first-dose COVID-19 vaccina- tion (0.618cases/100, 000vaccinations: 176 ChAdOx1 nCoV-19, 21 tozinameran, 1 mRNA-1273). First-dose ChAdOx1 nCoV-19 accounted for the excess of 98-140 GBS cases with a peak 24 days post-vaccination. First-dose tozinameran and second-dose any vaccination showed no excess GBS risk. The UK multicen- tre surveillance dataset (121 patients) identified no phenotypic or demographic differences between vaccine-linked and unlinked cases. First-dose ChAdOx1 nCoV-19 vaccination is associated with excess GBS risk 0.576 (95%CI 0.481-0.691) cases/100, 000 doses. No specific features are associated with vaccination-related GBS cases. The mechanism of immunogenicity of ChAdOx1 nCoV-19- warrants further study.